Geotecnologias aplicadas à análise do uso e cobertura da terra na Bacia Hidrográfica do Rio Itaqueri/SP - Fornazieiro, Marcos Paulo Almeida [UNESP] (2014)
This research aimed to analyze the evolution of land use and land cover vegetation Itaqueri river basin, located between the cities of Itirapina and Brotas, in the central portion of the State of São Paulo, due to the profund landscaped changes that the region has suffering the last few decades...